THE TRANSLATION OF FIXED EXPRESSION FROM FRENCH TO INDONESIAN IN 'MADAME BOVARY' NOVEL - Mubarok Dilma Fasa; Sajarwa Sajarwa (UIN Raden Mas Said Surakarta, 2021)
A fixed expression is a combination of words that has a stylistic value. The meaning of a fixed expression should be understood from the whole parts and cannot be identified from each of the constituent separately. This study aimed to identify the techniques used to translate French fixed expressions to Indonesian language based on the theory of translation techniques proposed by Molina and Albir (2004). It applied descriptive-qualitative method focusing on equivalence in translation. The data collection was carried out by finding the metaphorical suites of words in Gustave Flaubert’s Madame Bovary novel and their equivalents in its Indonesian version Nyonya Bovary. The results showed that, in total, there are three different techniques used by the translator in translating the fixed expressions in the novel. Out of 73 fixed expressions, 61 were translated by modulation, 8 by discursive creation and only 4 by transposition. This article is expected to give contribution to the studies of translation in general and translation of fixed expressions from French to Indonesian, in particular.